Melacak Pengaruh dan Pergeseran Orientasi Tamatan Kairo - Azra, Azyumardi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1995)
In the last view years there have emerged some new tendencies in studying Muslim societies. One of the most important of these is the study of religio-cultural exchange among the various Muslim societies in the world. There is a little doubt that this kind of study is both interesting and challenging. It involves not only a form of comparative study of the Muslim societies have influenced each other in the course of history.DOI: 10.15408/sdi.v2i3.832